The early modern invention of late antique Rome - Denzey Lewis, Nicola (Cambridge University Press, 2020)
"Deep in the Veneto countryside, travelers in the seventeenth and eighteenth century might easily bypass the Italian town of Monselice, overshadowed as it was by the graceful Renaissance cities of Padua and Ferrara. But fortunately for Monselice, the little hamlet had its own attraction that lured wayfarers who might not otherwise have bothered to scale the heights of the rocky promontory against which Monselice was poised if they were hastening between the two great cities which framed it. It was not the town's sturdy Duomo that drew people - any town of consequence had one of these - nor the castello that stubbornly topped the promontory with a crenellated crown; it was something quite unexpected that greeted a pious Christian pilgrim this close to the powerhouse of Venice: a microcosmic, sacred Rome artfully arranged according to a symbolic, secret order. A curving path up Monselice's mountain, just beyond its Duomo and city center, revealed a series of six identical chapels strung out like rosary beads. Each chapel represented - indeed, was metonymically identical to - six of Rome's seven great pilgrimage churches. As the faithful ascended Monselice's monte sacro, each chapel visit conferred a new papal indulgence, just as visiting the real pilgrimage churches in Rome did. The regular pulse of these tidy, white-stuccoed shrines - built, almost perversely, not to resemble Rome's churches but in the style of Roman pagan aediculae - continued up the curve until the sixth chapel brought its panting pilgrims, hearts pounding with exertion, up to a flat, open space marked out by regular, geometrical gardens, a surging fountain, a handsome and capacious villa, and the seventh chapel - different from the 2 rest, but in a significant sense, the jewel in the site's crown"--
Keywords: 30-600; Christian saints : Cult : Italy : Monselice : History; Church history : Primitive and early church, ca. 30-600; Christian saints : Cult; Church history : Primitive and early church; Monselice (Italy) : Church history; Rome (Italy); Italy : Monselice; Italy : Rome